The effectiveness of combination therapy with the use of natural factors in the treatment of patients with spine diseases in conjunction with ischemic heart disease and arterial hypertension - T. B. Bazzi; I. V. Deeva (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2016)
The approach to administration of balneo - mud treatment (BMT) for patients with hypertensive disease (HD) and ischemic heart disease (IHD) based on determination of severity and number of ischemic episodes in comparison with characteristic of rhythm disturbance according data of Holter monitoring, profile of circadian arterial pressure (AP) with circadian monitoring of AP has not yet received a sufficient spread in sanatorium-and-spa resorts of Crimea. This approach can be effective when choosing tactics of treatment at the spa, which leading factors are Saki lakepeloids. The correct assignment muds treatment and spa treatment in patients with hypertension can not only accelerate the achievement of target blood pressure, but also enhance the effectiveness of drug therapy. The good effect with stabilization of AD on the background of combined therapy has been obtained for 72 % of patients: in group of HD patients in 94 % cases; in IHD group with stable angina combined with HD in 51 % cases. AD patients characterized with significant decrease of activity of VNS sympathetic link, increased activity of parasympathetic ANS, decrease of the number of ischemia periods, decrease of episodes of extrasystolic arrhythmia. Use of peloids in the group of IHD patients with stable angina of 2nd functional class (FC), combined with HD of 1-2 stages can increase speed and magnitude of the night rise of AD and activity of sympathetic link of vegetative nervous system VNS, increase insignificantly the number of episodes of morning myocardial ischemia, and have arrhythmogenic effect.